Solvatochromic Dipolarity Micro-Sensor Behavior in Binary Solvent Sustems of the (Water + Ionic Liquid) Type. Application of Preferential Solvation Model And Linear Solvation Energy Relationships - Adam, Claudia Guadalupe (2014)
The type of specific intermolecular and interionic interactions that are established when an ionic liquid is dissolved in water was here analysed. The study of the solvatochromic response of dipolarity micro-sensors based on Reichardt ET(30) and Kamlet?Abboud?Taft solvent scales and the application of the solvent exchangemodel confirmed the formation of different intersolvent complexes in binary mixtures of (water + [C4mim] [BF4]/[Br]) type. These complexes provide H-bond or electron pairs to the polar network, respectively. Moreover, for 4-methoxybenzenesulfonyl chloride hydrolysis reaction in the (water + [C4mim] [BF4]) system, a higher inhibition (13 times) on the kobs values was observed. Multiple linear regression analysis that allows confirming the solvent effect upon the reactive system is due to the hydrogen-bond donor properties of intersolvent complex formed. Then, the correlation between two different solvent-dependent processes proved to be successful.